Are you there vodka? It's me, Chelsea - Handler, Chelsea (New York : Simon & Schuster, 2008)
The stand-up comedienne and star of such television programs as "Girls Behaving Badly" and "Chelsea Lately" celebrates the highs and lows of her life, from her relationships with a series of fetish-fulfilling paramours to an unorthodox dog-sitting stint.
Keywords: Man-woman relationships; Sex